1998
DOI: 10.1042/bj3300035
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the aspartic acid ligands in human serum transferrin: lobe–lobe interaction and conformation as revealed by antibody, receptor-binding and iron-release studies

Abstract: Recombinant non-glycosylated human serum transferrin and mutants in which the liganding aspartic acid (D) in one or both lobes was changed to a serine residue (S) were produced in a mammalian cell system and purified from the tissue culture media. Significant downfield shifts of 20, 30, and 45 nm in the absorption maxima were found for the D63S-hTF, D392S-hTF and the double mutant, D63S/D392S-hTF when compared to wild-type hTF. A monoclonal antibody to a sequential epitope in the C-lobe of hTF reported affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…The results of earlier cell binding assays suggested that iron removal from hTf results in a dramatic reduction of its receptor affinity (6)(7)(8)(9), while the results of more recent biophysical studies were consistent with a complete loss of the receptorbinding competence for the apo-hTf under conditions mimicking the extra cellular environment (11)(12)(13)(14). ESI MS provides conclusive evidence that aTf has the ability to form relatively stable complexes with TfR at neutral and mildly basic pH.…”
Section: Discussionsupporting
confidence: 50%
“…The results of earlier cell binding assays suggested that iron removal from hTf results in a dramatic reduction of its receptor affinity (6)(7)(8)(9), while the results of more recent biophysical studies were consistent with a complete loss of the receptorbinding competence for the apo-hTf under conditions mimicking the extra cellular environment (11)(12)(13)(14). ESI MS provides conclusive evidence that aTf has the ability to form relatively stable complexes with TfR at neutral and mildly basic pH.…”
Section: Discussionsupporting
confidence: 50%
“…Both groups used the Mabs as tools to study the interaction between hTf and the hTf receptor (hTf-R). In other work, Mason et al (1998) (www.interscience.wiley.com) DOI:10.1002/jmr.878 describe the use of a Mab named E-8 as a complementary tool for the analysis of conformational changes in the hTf molecule following iron binding by the iron-free apotransferrin isoform (apo-hTf ). However, until now the characterization of the antigenic surface of the hTf molecule and their potential uses in the above-mentioned studies have not been fully addressed.…”
Section: Introductionmentioning
confidence: 98%
“…Considerable interest has been focused to delineate the mechanism of iron release from transferrins in vitro, mainly by using small molecular weight chelators (9, 11-14, 16 -20), and, rarely, by using receptors (21)(22)(23). Because the iron release mechanism seems to be very complex with diferric transferrin, studies are now being undertaken using either independent lobes or selectively iron-loaded lobe on the full-length transferrin (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Because the iron release mechanism seems to be very complex with diferric transferrin, studies are now being undertaken using either independent lobes or selectively iron-loaded lobe on the full-length transferrin (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The iron-binding site on each lobe of transferrin involves two tyrosine residues, one each of aspartic acid and histidine residues.…”
mentioning
confidence: 99%
See 1 more Smart Citation